Exploring the influence of government controversies on the energy security and sustainability of the energy sector using entropy weight and TOPSIS methods - Georgia Zournatzidou; Christos Floros; Konstantina Ragazou (Economies, 2025)
In contemporary times, energy sustainability and security have become essential economic concerns globally. Nonetheless, in addition to these concerns, inadequate governance inside a corporation within the energy industry may result in corruption and energy instability within the sector. The primary purpose of this study was to examine the influence of a new array of corporate governance controversies on the energy security of 102 listed energy businesses in Europe. To achieve the purpose of this study, entropy weight and TOPSIS multicriteria approaches were used. The data were obtained from the Refinitiv Eikon database for fiscal year 2024. The findings reveal that the most significant influence, among the identified governance concerns that affect the energy security of European energy corporations, is the detrimental effect of the directors' people. Moreover, the criteria that constitute bribery, corruption, and fraud scandals seem to be the second most significant element affecting the energy security of the enterprises in this industry. The risk of corruption in governance is exacerbated in the realm of renewable energy due to several converging factors: the urgent demands to implement new projects in response to the climate crisis, apprehensions regarding energy security, potential access to lucrative contracts, and the existence of 'rent-seeking' gatekeepers within the processes central to the development and operation of renewable energy assets.
Keywords: 330; energy security; ESG; governance; corruption; sustainability; controversies